CTIM-24. RANDOMIZED TRIAL OF NEOADJUVANT VACCINATION WITH TUMOR-CELL LYSATE INDUCES T CELL RESPONSE IN LOW-GRADE GLIOMAS. (12th November 2021) - Taylor, Jennie; Ogino, Hirokazu; Nejo, Takahide; Gibson, David; Watchmaker, Payal; Okada, Kaori; Saijo, Atsuro; Tedesco, Meghan; Shai, Anny; Wong, Cynthia; Rabbitt, Jane; Olin, Michael; et al.
Abstract: BACKGROUND: The prognosis of WHO grade II low-grade gliomas (LGG) is varied with potential for long survival.Given their relatively intact immune system and slow growth rate, vaccines are an attractive treatment strategy for LGG in an attempt to defer more toxic treatments. The goals of this pilot study were to evaluate safety and immunological effects of vaccination with GBM6-AD, an allogeneic glioblastoma stem cell line lysate, with poly-ICLC in LGG. METHODS: Eligible patients were ≥ 18 years old, ≥ 70 KPS, with recurrent LGG or imaging consistent with LGG, and amenable to resection. Patients were randomized to vaccine prior to surgery (Arm 1) or not (Arm 2) and all received adjuvant vaccine. Co-primary outcomes were safety and immune response in the tumor, with exploratory outcomes of survival and immunologic effects in peripheral blood. RESULTS: A total of 17 eligible patients were evaluable – nine into Arm 1 and eight into Arm 2. Median age was 33 years, with median time from initial diagnosis of 4.7 years (0 – 20). Two patients (11.8%) previously received radiotherapy and seven (41.2%) prior systemic therapy. No dose limiting toxicities or grade 3 AEs were observed. Neoadjuvant vaccination induced up regulation of type-1 cytokines and chemokines in peripheral blood, and CD8+ T cell clones that reacted to the vaccine were also detected in the tumor. Median follow-up time from first post-operative vaccine was 20.8 months with median PFS of 11.0 months and time to change in therapy of 23.7 months. Of the six patients to receive additional treatment, three had second surgery only one confirming malignant progression to anaplastic oligodendroglioma. CONCLUSION: Treatment was well-tolerated with no regimen-limiting toxicity. GBM6-AD plus poly-ICLC induced effector CD8 + T cell response in peripheral blood and enables some vaccine-reactive CD8 + T cells to migrate into the TME. Further investigation is warranted.